A CONTROL SIMULATION OF AC-DC BUCK BOOST CONVERTER WITH PROPORTIONAL INTEGRAL DERIVATIVE (PID) USING MATLAB SIMULINK - Ahmad Faisal; Pristisal Wibowo; Dahril Satria Dandy (Sean Institute, 2023)
Converters are widely used in electric power systems, converters consist of several types, one industrial world and power electronics so that engineers conduct research and development to find out the quality of the power produced because power quality is one of the important parts in the electric power system. This research includes simulating the AC-DC buck boost converter using Proportional Integral Derivative (PID) control, from the simulation results show that the PID control on the AC-DC buck boost converter shows that it is able to maintain the power factor (PF) on the input side of the AC-DC buck boost converter obtained from the display of the calculation of the power factor value in the simulation circuit but there is still overshoot, rise time and peak time. the greater the reference voltage given will produce a greater rise time and peak time.of which is the AC-DC converter, the use of AC-DC converters will continue to increase both in the